(untitled) (Research, Society and Development, 2022)
The Community Therapy can be defined as a community space where life experiences and wisdom are shared. Objective to report the experience, importance and effectiveness of Community Therapy in the health-disease process, through the experiences of students of the Medicine and Psychology course at the University of Fortaleza, scholarship holders of the PET-SAÚDE Interprofessional Education Tutorial Program. It consists of an experience report, in which the practice was carried out at the Luís Franklin primary health care unit, in Messejana, in Fortaleza – Ceará, where a nurse from the Family Health Strategy Works as a community therapist and a Community Health Agent has been working as a co-therapist in this process for 3 years, and, through a structured questionnaire, several reports of positive experiences of the participants were verified and the importance of community therapy in the lives of these patients. Participants in the analyzed group responded that they felt they belonged to it and described the environment as a place of reception, appreciation, tranquility, joy, security and peace. In this way, it is concluded that community therapy consists of an effective integrative and complementary practice that is easy to implemented in Primary Care, helping to deal with the diverse and complex demands present in the Brazilian social context.